Digital preventive measures for arterial hypertension (DiPaH) – a mixed-methods study protocol for health services research - Bruch, Dunja; Muehlensiepen, Felix; May, Susann; Wengemuth, Eileen; Johannsen, Olen; Reber, Katrin Christiane; Blankenstein, Eva-Lotta; Fleige, Gerrit; Middeke, Martin; Albes, Johannes; Heinze, Martin; Lehnen, Marc; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Digital health measures promise to further improve the quality of cardiovascular care but have not yet been widely implemented in routine care. The research project Digital preventive measures for arterial hypertension (DiPaH) will systematically identify structural and individual factors in different stakeholders that influence the use of digital preventive measures in patients with arterial hypertension in Germany. Special focus is given to remote and sparsely populated areas, the age-specific impact, as well as influence of digital health literacy. Methods and analysis The DiPaH project is an exploratory cross-sectional study with a mixed-methods design, in which written surveys and interviews with patients and physicians will be conducted. In addition, secondary data from a health insurance company will be analyzed. In module 1, individuals from the database of the health insurance company with confirmed arterial hypertension will be interviewed (1,600 questionnaires, 30 interviews). Module 2 includes users of digital prevention offers and apps (400 questionnaires, 40 interviews) and in module 3, family physicians and cardiologists will be interviewed (400 questionnaires, 40 interviews). In a final module, the overall results will be analyzed and recommendations for interventions in clinical care will be derived. Discussion The DiPaH project will contribute to a patient-oriented and demand-based improvement of arterial hypertension prevention services in health care. Challenges and barriers will be analyzed and the respective target groups identified based on their prevention needs and social characteristics to enable a patient-centered implementation of digital prevention of arterial hypertension and cardiovascular services in general, and finally to improve cardiovascular outcomes. Clinical trial registration https://drks.de/search/de/trial/DRKS00029761, identifier DRKS00029761.